Assessing the Impacts of Climate Change on Livelihoods in Rujumbura Rukungiri District. - Niwagaba, Alfred (Kabale University, 2023)
Globally climate change effects are increasing and it affects the whole globe. Sub-Saharan Africa is more vulnerable and the most exposed to these effects. In most African countries including Uganda, agriculture is the leading source of livelihood and is the most affected sector. This study explored the impacts of climate change on the livelihood sources, the people’s perceptions and the adaptation and coping measures. The study was carried out in n the sub counties of Ruhinda, Buhunga, Nyakagyeme and Bugagari. In addition, the objectives of the study were: 1) to assess the impacts of climate change on peoples’ livelihoods, to analyze the perception of farmers about climate change impacts on peoples’ livelihoods, 3) to determine the adaptation measures used by people to reduce the climate change impacts on people’s livelihoods. The data was collected using interview guides and questionnaires, the respondents reported that climate change was due to deforestation, wetland degradation, and bush burning. The major livelihood sources of people in the areas were crop growing, livestock farming, trading activities and handcrafts like basket weaving. Drying of crops, water scarcity, increased crop pests, soil erosion and reduced yields are the most experienced impacts resulting from climate change. The most affected crops were beans, cassava, maize, banana, potatoes, coffee and rice. On the climate change perceptions, there has been increase in drought conditions, variations in seasons, increase in temperatures, decrease in rainfall, erratic rains and increased flooding conditions. Adaptation measures used by respondents were; early planting, changing the planting dates, crop diversifications, change in the crop varieties, rainwater harvest, and watering crops during drought. Meanwhile, livestock farmers reported shift grazing and change of local varieties as their mitigation actions to the climate change conditions. These challenges were limited capital to purchase improved agriculture technologies, limited skills and lack of enough government support. Recommendations of the study are the following: training the locals on the mitigation measures and extending credit facilities to enable farmers to access improved agriculture technologies.